Management Actions Promote Human-Wildlife Coexistence in Highly Anthropized Landscapes: The Case of an Endangered Avian Scavenger - Zuberogoitia, Iñigo; Morant, Jon; González-Oreja, José Antonio; Martínez, José Enrique; Larrinoa, Mikel; Ruiz, Julio; Aginako, Igor; Cinos, Cristina; Díaz, Eneko; Martínez, Fran; Galarza, Aitor; Pérez de Ana, Juan Manuel; et al. (Frontiers in Ecology and Evolution, 2021)
Anthropized landscapes are characterized by various human activities related to resource extraction, leisurerecreational activities, and urbanization, among others. Conservation of species living in such landscapes is challenging due to the lack of compatibilizationcompatibility between wildlife and human needs, which can provokecreate win-lose scenarios for target species. Therefore, adequate management practices are necessary to reduce conflicts and promote the coexistence between wildlife and human beings. In this study, byHere, using long-term monitoring data (2000-2020), we test the effectiveness of management measures on the productivity of an Egyptian vulture population living in an anthropized region of Northern Spain by using long-term monitoring data (2000-2020). During the first decade, we proved demonstrated that disturbing activitiesdisturbance events negatively affected the species reproduction. Therefore, in 2010 we started a management plan in which we first established a basis for the species protection, and second we developed management actions to avoid or reduce the impact of potential disturbing activitiesdisturbance events on the Egyptian vulture’ breeding. We observed that almost half of the disturbances detected after the management was related to resource extraction activities such as forestry (40.6%). Management measures effectively increased productivity (84 vs 137, chicks fledged successfully before and after, respectively) and the breeding success of the pairs in which the disturbances were detected and stopped (66.7%) was much higher than those non-managed and non-stopped in time (17.4%). Moreover, we estimated that 44 nestlings (32.8%) would have died without management actions during the second decade. Overall, our work demonstrated that collaborative networks can design and implement effective management measures for endangered territorial species, taking into account all agents involved (policymakers, rangers, stakeholders, general public and researchers) in the conservation area. Thereby, it alleviates conflicts in human-dominated ecosystems and generates a balanced scenario that favors long-term sustainable human-wildlife coexistence.